STRES PADA ORANG TUA YANG MEMILIKI ANAK DENGAN GANGGUAN SPEKTRUM AUTISME - Asri Mutiara Putri; Woro Pramesti; Rani Dwi Hapsari (JURNAL PSIKOLOGI MALAHAYATI, 2019)
STRESS EVALUATION IN PARENTS OF CHILDREN WITH AUTISME SPECTRUM DISORDERIntroduction: Autism spectrum disorder (ASD) is a developmental disorder with symptoms like abnormalities in social function, communication, language, and repetitive behavior. Children with ASD) have many difficulties and developmental problem which can lead to stress in parents.Purpose: The aim of this study wastodescribethe stres level ofparentsofchildren with autism spectrum disorder on disable school in Bandar Lampung.Method: This study is a quantitative research with observational survey design. The sample is 39 parents of children with ASD that goes to disable school in Bandar Lampung. Perceivd Stress Scale (PSS) is used to assess stress.Results: Result obtained form 39 parents, found that most of the parents have low level of stress (59%), followed with moderate level of stress (35,9%), and the least was high level of stress (5,1%).Conclusion: Although low level of stress found in this study, parents of children with ASD still need support from social environment to give good parenting for their children.Pendahuluan: Gangguan Spektrum Autisme (GSA) merupakan gangguan perkembangan dengan gejala antara lain abnormalitas pada fungsi sosial, komunikasi dan bahasa, serta perilaku repetitif. Anak penyandang GSA mengalami berbagai hambatan dan masalah dalam perkembangannya sehingga dapat menjadi sumber stres bagi orang tua.Tujuan: Tujuan dari penelitian ini adalah untuk mengetahui gambaran stres pada orang tua yang memiliki anak dengan gangguan spektrum autisme di SLB se-Bandar Lampung.Metode: Penelitian ini merupakan penelitian kuantitatif dengan desain survey observasional. Sampel penelitian berjumlah 39 orang tua dari anak penyandang GSA yang bersekolah di SLB di Bandar Lampung. Perceived Stress Scale (PSS) digunakan sebagai alat ukur untuk menilai stres.Hasil: Hasil yang didapatkan dari total responden sebanyak 39 orang tua, sebagian besar responden memiliki tingkat stres ringan (59%), diikuti dengan stres sedang (35,9%), dan paling sedikit mengalami stres berat (5,1%). Simpulan: Meskipun ditemukan bahwa stres yang dialami tergolong ringan, orang tua dari anak penyandang GSA tetap membutuhkan dukungan dari lingkungan untuk dapat memberikan pengasuhan yang baik bagi anaknya.